Utility of nociceptive flexion reflex threshold and bispectral index to predict movement responses under propofol anaesthesia. (3rd April 2017) - Jakuscheit, Axel; Posch, Matthias J.; Gkaitatzis, Stefanos; Neumark, Lisa; Hackbarth, Mark; Schneider, Martin; Lichtner, Gregor; Baars, Jan H.; von Dincklage, Falk
Abstract: Introduction: The nociceptive flexion reflex threshold (NFRT) is a promising tool to monitor analgesia during general anaesthesia. Clinical studies have shown that the NFRT allows to predict movement responses to painful stimuli under a combined anaesthetic regime of sedative and opioid agents. Experimental studies indicated that the NFRT is also able to predict such movement responses under an exclusively sedative regime like propofol mono-anaesthesia. Therefore, we performed this study to investigate the ability of the NFRT to predict movement responses to painful stimuli in patients during a clinical propofol mono-anaesthesia. Methods: We investigated 140 cardiac surgery patients during their postoperative phase under propofol mono-anaesthesia. NFRT and bispectral index (BIS) were determined in each patient right before endotracheal suctioning or painful electrical test stimulation. Prediction probabilities were calculated to quantify how accurate each measure is able to predict movement responses to the stimuli. Results: The 124 patients included in the analysis received a median propofol dosage of 3.2 (2.5–3.9) [median (IQR)] mg/kg/h. The included patients showed 287 movement responses after a total of 725 investigated stimuli. The prediction probabilities for positive movement responses were 0.63 (95%CI: 0.59–0.67) for the NFRT and 0.69 (95%CI: 0.65–0.73) for the BIS. Conclusions: The NFRT allows the prediction of movement responses under propofol mono-anaesthesia, which confirms its utility as a monitor to predict movement responses under general anaesthesia. The BIS allows an even more accurate prediction, although it does not reflect the physiological structures of movement suppression, but correlates closely with the dose of propofol. Trial registration: German clinical trial register (DRKS00003062, Deutsches Register Klinischer Studien).